The Fidelity of Reason: A Phenomenological Metaphysics of Self, Nature and Divinity - Ó Murchadha, Felix (Contributions to Phenomenology, In Cooperation with The Center for Advanced Research in Phenomenology, 2025)
XV, 323 p.